Municipal Wastewater Treatment Using Enhanced Iron Slag Pervious Concrete - Teymouri, Ehsan; Wong, Kwong Soon; Davis, Taylor (Journal of Environmental Treatment Techniques, 2025)
Municipal wastewater should be treated properly before being discharged into the environment; however, due to high expenses, it might be unattainable, particularly for developing countries. This study investigates the application of enhanced iron slag pervious concrete (EISPC), an economical and sustainable approach for treating municipal wastewater before being discharged into the environment, where it does not meet the criteria of environmental standards. Consequently, three rectangular cube canals (2 m in length, and 0.3 m in width and height) were constructed and filled with EISPC with a mixture of 100% coarse aggregate iron slag (4.75-9.5 mm). Subsequently, a continuous flow rate of wastewater was entered into these canals with a flow rate of 100 l/hr. Wastewater traveled through canals and its quality was evaluated upon exiting the canals over a week, with evaluations conducted every 24 hours. The results showed that EISPC effectively reduced the chemical oxygen demand (COD), biochemical oxygen demand (BOD), and total suspended solids (TSS) by about 45%, 80%, and 75% at the first sampling, and 25%, 65%, and 50% at the end of the experiment, respectively. The primary mechanism for pollutant removal was the physical entrapment of contaminants within the interconnected pores of EISPC and the porous structure of the iron slag aggregates. Also, the results of scanning electron microscopy (SEM) images proved satisfactory trapping of pollutants and efficiency of EISPC for further application in wastewater treatment plants.